Routine frailty assessment predicts postoperative complications in elderly patients across surgical disciplines - A retrospective observational study - Birkelbach, Oliver; Moergeli, Rudolf; Spies, Claudia; Olbert, Maria; Weiss, Bjoern; Brauner, Maximilian; Neuner, Bruno; Francis, Roland C. E.; Treskatsch, Sascha; Balzer, Felix (BMC Anesthesiology, 2019)
Background: Frailty is a frequent and underdiagnosed functional syndrome involving reduced physiological reserves and an increased vulnerability against stressors, with severe individual and socioeconomic consequences. A routine frailty assessment was implemented at our preoperative anaesthesia clinic to identify patients at risk. Objective: This study examines the relationship between frailty status and the incidence of in-hospital postoperative complications in elderly surgical patients across several surgical disciplines. Design: Retrospective observational analysis. Setting: Single center, major tertiary care university hospital. Data collection took place between June 2016 and March 2017. Patients: Patients 65 years old or older were evaluated for frailty using Fried's 5-point frailty assessment prior to elective non-cardiac surgery. Patients were classified into non-frail (0 criteria, reference group), pre-frail (1-2 positive criteria) and frail (3-5 positive criteria) groups. Main outcome measures: The incidence of postoperative complications was assessed until discharge from the hospital, using the roster from the National VA Surgical Quality Improvement Program. Propensity score matching and logistic regression analysis were performed. Results: From 1186 elderly patients, 46.9% were classified as pre-frail (n = 556), and 11.4% as frail (n = 135). The rate of complications were significantly higher in the pre-frail (34.7%) and frail groups (47.4%), as compared to the non-frail group (27.5%). Similarly, length of stay (non-frail: 5.0 [3.0;7.0], pre-frail: 7.0 [3.0;9.0], frail 8.0 [4.5;12.0]; p < 0.001) and discharges to care facilities (non-frail:1.6%, pre-frail: 7.4%, frail: 17.8%); p < 0.001) were significantly associated with frailty status. After propensity score matching and logistic regression analysis, the risk for developing postoperative complications was approximately two-fold for pre-frail (OR 1.78; 95% CI 1.04-3.05) and frail (OR 2.08; 95% CI 1.21-3.60) patients. Conclusions: The preoperative frailty assessment of elderly patients identified pre-frail and frail subgroups to have the highest rate of postoperative complications, regardless of age, surgical discipline, and surgical risk. Significantly increased length of hospitalisation and discharges to care facilities were also observed. Implementation of routine frailty assessments appear to be an effective tool in identifying patients with increased risk. Now future studies are needed to investigate whether patients benefit from optimization of patient counselling, process planning, and risk reduction protocols based on the application of risk stratification.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Elderly; Frailty; Outcome; Perioperative